Da-Cheng-Qi Decoction Combined with Conventional Treatment for Treating Postsurgical Gastrointestinal Dysfunction. (15th May 2017) - Jin, Wei; Li, Qingjie; Luo, Xiaoqiong; Zhong, Juan; Song, Yang; Li, Yiwei
Abstract : Aim . To assess the current clinical evidence of the effectiveness of Da-Cheng-Qi Decoction (DCQD) for the treatment of Postoperative gastrointestinal dysfunction (PGD). Methods . Randomized controlled trails (RCTs) of Da-Cheng-Qi Decoction (DCQD) to PGD were searched from available major electronic databases to September 2016. The intervention must be a modified DCQD or DCQD integrated to Western Medicine (WM) compared with WM or placebo or blank. The main outcome index was clinical effectiveness and improvement of major symptoms. Data extraction, data analysis, and methodological quality assessment are conducted according to the Cochrane Handbook for Systematic Review of Interventions, version 5.0.2. RevMan 5.3 software was applied to our data analyses. Results . Seven RCTs involving 494 participants were recruited and identified. The methodological quality of all trials were assessed and generally of low-level. Those studies were published between 2004 and 2013. All 7 studies which used herbals (modified DCQD) integrate WM in test group compared with WM as the intervention and only one study (Sunyouxu 2013) integrates placebo to Western Medicine as the control group intervention. The treatment course was 1 week to 2 weeks. Evaluation of intervention effectiveness consists of the clinical effective rate indicator and the PGD symptoms indicator including time of borborygmus, time of gastrointestinal exhaust, and time of defecate. The clinical effectiveness results are beneficial to the test group. Conclusion . DCQD could improve PGD symptoms and promotion clinical effectiveness.